1976
DOI: 10.1128/aac.9.4.600
|View full text |Cite
|
Sign up to set email alerts
|

Minocycline Resistance in Staphylococcus aureus: Effect on Phage Susceptibility

Abstract: Tetracycline-resistant strains ofStaphylococcus aureus are minocycline sensitive, with the exception of strains susceptible to phages ofthe 83A/84/85 complex and some methicillin-resistant strains of other phage types. Strains of the 83A/ 84/85 complex yield mutants with increased mimocycline resistance. Transduction of minocycline resistance into the susceptible strain RN 450 was obtained with donor strains possessing either markers for both extrachromosomal tetracycline resistance (tet) and chromosomal tetra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
16
0

Year Published

1979
1979
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 30 publications
(29 reference statements)
0
16
0
Order By: Relevance
“…The the three Mecr donor strains indicated that the presence of minocycline resistance is indicative transductants lost their susceptibility to interof the chromosomal location of the tetracycline national typing phages 6, 42E, 53, 54, 75, 83A, resistance marker (22). Genetic transfer was at-and 85, but retained susceptibility to experimentempted with phages induced in Mecr strains tal phages 89 and 92 and, to a lesser degree, to and phage preparations obtained by propagation phages 88 and 90.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The the three Mecr donor strains indicated that the presence of minocycline resistance is indicative transductants lost their susceptibility to interof the chromosomal location of the tetracycline national typing phages 6, 42E, 53, 54, 75, 83A, resistance marker (22). Genetic transfer was at-and 85, but retained susceptibility to experimentempted with phages induced in Mecr strains tal phages 89 and 92 and, to a lesser degree, to and phage preparations obtained by propagation phages 88 and 90.…”
mentioning
confidence: 99%
“…tion of chromosomal tetracycline resistance is The Mecr transductants retained the phage susaccompanied by loss of susceptibility to several ceptibility of the acceptor strain 8825 P524. The typing phages such as 6, 47, or 75 and retention transduction experiments were repeated by usof susceptibility to phages 83A and especially 85 ing tetracycline-resistant transductants from (21,22 In contrast to the majority of Mecr Staphylococcus strains described in the literature (1, 24), with the exception of strain VIII, all Mecr strains tested possess homogeneous methicillin resistance, resulting in similar zone sizes at 30 and 37°C. Strain VIII was also the only strain found to be lipase negative.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For transfer on solid medium, 0.1 ml of the control cultures and 0.1 ml of an equal mixture of the two strains were plated on LB agar. After overnight incubation, suspensions of approximately 5 x 108 cells in LB broth were plated on LB medium with 3 ,ug of novobiocin and 2 jig of rifampin per ml (NR media) and the following concentrations of antibiotics: tetracycline, 2.5 ,ug/ml; erythromycin, 20 ,ug/ml; clindamycin, 5 ,ug/ml; methicillin, 10 ,ug/ml; penicillin, 10 ,ug/ml; gentamicin, 10 ,ug/ml; streptomycin, 50 ±g/ml; kanamycin, 25 ,ug/ml; chloramphenicol, 30 p.g/ml; and Cd(NO3)2, 2 x 10-5 M. In some instances, antibiotic media with novobiocin but without rifampin were used.…”
Section: And Methodsmentioning
confidence: 99%
“…After reisolation, nonlysogenic colonies were tested for sensitivity to phage 188 and for lack of phage production after induction with mitomycin C. Transduction procedures. Transduction procedures were performed as described previously (10). The transducing phage was added at a multiplicity of 0.1 to 0.2 PFU per colony-forming unit (CFU).…”
Section: And Methodsmentioning
confidence: 99%